2017
DOI: 10.1140/epjc/s10052-017-5124-y
|View full text |Cite
|
Sign up to set email alerts
|

Generalized spheroidal spacetimes in 5-D Einstein–Maxwell–Gauss–Bonnet gravity

Abstract: The field equations for static EGBM gravity are obtained and transformed to an equivalent form through a coordinate redefinition. A form for one of the metric potentials that generalizes the spheroidal ansatz of Vaidya-Tikekar superdense stars and additionally prescribing the electric field intensity yields viable solutions. Some special cases of the general solution are considered and analogous classes in the Einstein framework are studied. In particular the FinchSkea ansatz is examined in detail and found to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Pandya et al [27] found models with geometry consistent with observed radii and masses for dense stars. The Finch-Skea geometry has also been studied for higher dimensional gravitational geometries [28][29][30][31] and trace-free gravity [32].…”
Section: Finch-skea Geometrymentioning
confidence: 99%
“…Pandya et al [27] found models with geometry consistent with observed radii and masses for dense stars. The Finch-Skea geometry has also been studied for higher dimensional gravitational geometries [28][29][30][31] and trace-free gravity [32].…”
Section: Finch-skea Geometrymentioning
confidence: 99%
“…Plugging in the typical values from Eqs. (23)(24)(25), and using the above expressions, we get the different forces in a straightforward way, which leads to:…”
Section: Equilibrium Conditionmentioning
confidence: 99%
“…The EGB facilitates a natural generalization of GR to higher dimensions. [ 26 ] This is achieved by including higher curvature while preserving the fundamental elements of GR such as the conservation laws via the Bianchi identities, diffeomorphism invariance and quasi‐linear, second order equations of motion. It is well‐known that the EGB theory is a special case of the Lovelock [ 27 ] theory arising from the Nth order Lovelock Lagrangian.…”
Section: Introductionmentioning
confidence: 99%